The American Soul Rush : Esalen and the Rise of Spiritual Privilege - Goldman, Marion S. (Book collections on Project MUSE., 2012)
"The American Soul Rush explores the concept of spiritual privilege and Esalen's foundational influence on the growth and spread of diverse spiritual practices that affirm individuals' self-worth and possibilities for positive personal change. The book also describes the people, narratives, and relationships at the Institute that produced persistent, almost accidental inequalities in order to illuminate the ways that gender is usually central to religion and spirituality."--Jacket